Technique of training of inspiratory muscles for the girl with a neurocirculatory dystonia - Levchenko V.A; Vakalyuk I.P; Dosyn D.A (Kharkov National Pedagogical University, 2010)
New unmedicinal approach is created for a removal or diminishing of displays of a hypervent syndrome at a cardiophyshoneurosis for young people by optimization of inciter effort. 52 girls are inspected by age 17-19 years. All patients during the last year not systematic accepted medical preparation without a long clinical effect. Training of inciter muscles by the systematic dosed inciter tension improves the indexes of the external breathing, increases a diaphragm excursion.